The Ancient Pergamos Project: Fieldwork report for 2024 - Klingborg, Patrik; Galani, Georgia; Dadaki, Stavroula; Malama, Penelope (Opuscula. Annual of the Swedish Institutes at Athens and Rome, 2025)
The aim of this paper is to report on the fieldwork conducted at Pergamos in 2024, in order to make the data available and to provide preliminary observations and interpretations of the finds. In the absence of any previous archaeological work at the site, the main objective of this first fieldwork season was to construct a basic chronological framework of human presence and activity. To this end, a systematic surface survey was carried out, providing an overview of the material, along with excavations in the lower terrace of the hill of Koules/Alonaki, in connection to the better-preserved southern fortification walls. The architectural elements and the finds unearthed revealed important, previously unknown, aspects about ancient Pergamos, embracing a variety of activities and indicating connections with both the local/regional material culture but also with that of regions further away.